Um Mecanismo Eficiente de Controle de Congestionamento para Redes Tolerantes a Atrasos e Desconexões - Naves, Juliano F.; Moraes, Igor M. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2017: Anais do XXXV Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2017)
Routing protocols for Delay and Disruption Tolerant Networks frequently use message replication in order to increase the network resilience and the message delivery rate. However, uncontrolled replication may lead to network congestion, negatively impacting network performance. This paper proposes a simple and efficient hybrid network congestion control mechanism that aims at avoiding unwanted message replication and to reduce network congestion. The proposal is based on the fact that the removal of messages from nodes buffers must be persistent, i.e. a node must not receive messages that have already been removed from its buffer again. The analysis consider four real mobility traces and three well-known routing protocols. Results show the proposed mechanism reduces transmission overhead in up to 98.5% in addition to increasing delivery rate and decrease delivery latency.